PENGARUH PELEMBAGAAN DESA BUDAYA PAMPANG - Arifin, M. Bahri; Vivian, Yofi Irvan; Nasrullah, Nasrullah (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
Pampang is a cultural tourism village in Samarinda, East Kalimantan. Most of Pampang’s people do the art activities. Every Sunday at 02.00 pm in Lamin, there is a dance performance of Dayak Kenyah. Three Sapeq players become a partner in this dance. The existence of this activity becomes the first step of Cultural Tourism Village of Pampang. A strong institutionalization that is able to reconstruct a village becomes a brand as cultural village. In this research, the writer analyzed process and dynamic of the institutionalization in Cultural Tourism Village of Pampang using theories of Cultural Phase’s van Peursen, commodification, cultural industry’s Frakfurt School and mediatization.Keywords: process, transformation, institutionalization, Cultural Tourism Village of Pampang